2009
DOI: 10.1016/j.ejso.2009.02.018
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of dual-isotope lymphoscintigraphy for breast sentinel node biopsy comparing intradermal and intraparenchymal injection

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Periareolar intradermal contrast injections can cause minor tissue injury, namely superficial erythema and blistering at the injection site. We found that tissue injury at the injection sites was temporary and reactions fell within the expectations of clinical experience [28] Moreover, no irreversible or unexpected adverse events have been reported in prior contrast-enhanced MRL studies, which is confirmed by our observations [10,12,13,29,30]. …”
Section: Discussionsupporting
confidence: 85%
“…Periareolar intradermal contrast injections can cause minor tissue injury, namely superficial erythema and blistering at the injection site. We found that tissue injury at the injection sites was temporary and reactions fell within the expectations of clinical experience [28] Moreover, no irreversible or unexpected adverse events have been reported in prior contrast-enhanced MRL studies, which is confirmed by our observations [10,12,13,29,30]. …”
Section: Discussionsupporting
confidence: 85%
“…However, the meta‐analysis clearly demonstrated that significantly fewer extra‐axillary SLNs were identified on superficial injection of radioactive tracer compared with deep injection. This contradicts the accepted notion that the lymphatic drainage of the breast parenchyma and areola converge at the first‐ or second‐echelon nodes in the axilla. It suggests that the drainage of the breast is more variable than previously thought, with the parenchymal lymphatics having interconnections with perforating lymphatic vessels, which pierce the intercostal fascia and terminate within the IMNs.…”
Section: Discussionmentioning
confidence: 71%
“…The discordance between SLNs identified using superficial and deep injections of radioactive tracer was examined in six studies ( Tables and ). The discordance ranged between 4 per cent and 73 per cent for axillary mapping, and 0 per cent and 61 per cent for internal mammary node (IMN) mapping. Noushi et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations